FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN YANG TERDAFTAR DI BEI - Natasia, Weka; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test some factors which has influenced the debt policy in the manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in the 2009-2013 periods. The samples are 83 manufacturing companies with sample selection characteristic which has been carried out by using the purposive sampling method. The multiple linear regressions analysis is used as the data analysis. The result of the research describes that free cash flow, managerial ownership, profitability, assets structure, retained earnings and liquidity have influence to the debt policy whereas the institutional ownership and companyâs growth does not have any significant influence to the debt policy.Keywords: Determinant, Pecking Order Theory, Debt Policy